Assessment of HIV/AIDS Risk Behaviors among Secondary School Students in Adamawa State - Isaac John Umaru; Solomon O. Asare; Tyem Lawal Danjuma; Inemesit Samuel Essien; Ingwu Joseph Akem; Usenobong Morgan Akpan; Julius Ishaya Salman; Kwabena Owusu Amoah; Evelyn Ovenomo Tony-Enwin; Hauwa A. Umaru; Maryam Usman Ahmed (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2026)
Adolescents in Nigeria are increasingly exposed to HIV/AIDS risk behaviors due to socio-economic challenges, peer influence, and limited access to sexual health education, with secondary school students in Adamawa State particularly vulnerable to early sexual debut, multiple sexual partnerships, and inconsistent condom use. This study aimed to assess the prevalence of HIV/AIDS risk behaviors among secondary school students in Adamawa State, examine the socio-demographic factors associated with these behaviors, and evaluate students’ knowledge and perceptions of HIV/AIDS transmission and prevention. A cross-sectional survey design was employed involving 300 secondary school students selected through stratified random sampling. Data were collected using a structured questionnaire covering demographic characteristics, sexual behavior, substance use, and HIV/AIDS knowledge, and were analyzed using descriptive statistics and chi-square tests. The findings showed that 30% of students experienced peer pressure to engage in sex, 28% had already had sexual intercourse, 19% reported multiple sexual partners, 18.3% admitted inconsistent condom use, 14% used substances before sex, and 12% engaged in transactional sex. Knowledge gaps were also evident, as only 70% recognized condom use as a preventive measure and 25% incorrectly believed that HIV is curable. Socio-demographic factors, including age (18–19 years), male gender, senior class level, and single-parent family structure, were significantly associated with risky sexual behavior (p < .05). These findings underscore the urgent need for comprehensive sexual education, peer mentorship programs, and improved access to sexual health resources in secondary schools. The study contributes contextual evidence on adolescent HIV vulnerability in Adamawa State and highlights the importance of addressing socio-demographic risk factors and misconceptions about HIV/AIDS to reduce risky behaviors and promote adolescent health.